Architectural patrimony in the graphical representation of the Voisin Plan. Issue 3 (2nd July 2016) - Velasquez, Victor
Abstract: The "Plan Voisin" for Paris dated 1925, is one of the most notorious urban projects by Le Corbusier. In it he implements his first real model of the modern city: "The city of Three Million Inhabitants", drawn for the Autumn Exhibit on 1922. Both projects have a close and direct relation. While one proposes a theoretical model, the other develops how to implement it in the center of Paris. Therefore, both projects can be understood as the same approach but in two different moments. In Le Corbusier's books, the graphical representation of the projects reflect this, although the documents tend to contradict it. In his "Œuvre complète", for example, the number of images differs for each case. While the project "The city of three million Inhabitants" is represented by a generous amount of drawings and plans (around 20 images), the "Plan Voisin" adds up to a maximum of five specific images. In the book "Urbanisme" the proportion is of images is similar. This This is a cause of scarce comprehension of the plan for Paris. The article focuses on the graphical documentation in "Plan Voisin", its difference with the theoretical model and an analysis of its implementation. Principally, the article studies the relation between the new buildings with with those that remains, revealing Le Corbusier's criteria towards architectural heritage and the importance he gives to some urban complexes in Paris.